343 Addressing community violence through training: rukajuu beekeeping pilot intervention in dar es Salaam, Tanzania. (1st September 2016) - Outwater, Anne H; Kazaura, Method; Abraham, Alison G; Msemo, Stephen; Sekai, Linda Helgesson; Iseselo, Masunga; Killewo, Japhet
Abstract : Background: More than half of DSM, Tz. homicides are a result of community violence. In 2005, it was found, those most at risk for homicide death are: male Tanzanians, aged 20–35 years, lack of employment/education, caught stealing sale-able goods such as cell phones, purses, and domestic meat animals. Most deceased had family responsibilities. The most malleable variable is: lack of employment/occupation. The objective of this research is to gain insight into ways to operationalize interventions designed to improve income generation of at-risk youth. Methods: This pilot study will use pre-test post-test design with four interventions: Introduction + Health training (2 sessions) Introduction + Health + Entrepeneurship training ( 6 sessions) Introduction + Health + Beekeeping training (6 sessions) Introduction + Health + Beekeeping + Entrepeneurship training (10 sessions) Intervention started April 2015 and will be completed January 2016. Post intervention data will be collected 3, 6 and 12 months after the last session. As a pilot study, evaluation variables include: availability/cooperation of subjects, research collaborators and institutions, timing, facilities and equipment needed, researcher experience, and costs. Results: Four youth camps were randomly chosen from 243 mapped camps in 4 wards of DSM. Fifteen members of each camp were invited to join. At the introductory session, camps were randomly chosen for intervention arms. Baseline data were collected quantitatively: demographics, health parameters, assets, risk for violence, and reading, writing, math skills. And qualitatively : involvement with community violence, income generation practices, money spending patterns, helpful and deviant deeds, aspirations. Conclusions: This pilot research is providing insight needed to conduct an experimental study to examine sustainable ways to reduce community violence. It builds on government and NGO youth employment initiatives; it is giving insight as to how such initiatives can be most effective.